Formulasi dan Evaluasi Fisik Minyak Massage Terapi Berbasis Kombinasi Minyak Nabati dan Minyak Atsiri - Kadek Dyah Regita Wulandari Wijaya (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
This study aims to formulate and evaluate a therapeutic massage oil preparation based on a combination of vegetable and essential oils as a topical relaxation product. The formulation was prepared from a mixture of Virgin Coconut Oil (VCO), olive oil, jojoba oil, peppermint oil, and rose oil, with the addition of Butylated Hydroxytoluene (BHT) as an antioxidant. The preparation process was carried out using a stepwise mixing method until a homogeneous mixture was obtained. Physical evaluations included organoleptic tests, pH measurement, and viscosity analysis. The results showed that the preparation had a slightly thick liquid form, a pale yellow color, and a distinctive aroma of combined rose and peppermint oils. The pH value of 5.38 was within the normal skin pH range (4.5–6.5), indicating its safety for topical use. The viscosity value of 77.3–79.2 cP indicated relatively high thickness while maintaining comfort during massage. Overall, the preparation was organoleptically stable, safe for the skin, and showed potential as a therapeutic massage oil product with relaxation and moisturizing effects.